Efektivitas Dosis Ekstrak Kulit Pisang Kepok (Musa Paradisiaca Var. Balbisiana colla) terhadap Jumlah Leukosit Tikus Putih (Rattus norvegicus) yang Diinduksi Escherichia coli - Hertama Pandiangan, Grace; Chairul, Muhammad; Novita Pane, Herlin (Jurnal Pendidikan Indonesia, 2025)
This study aims to determine the effectiveness of various doses of kepok banana peel extract (Musa paradisiaca var. balbisiana Colla) on the number of leukocytes of white rats (Rattus norvegicus) induced by Escherichia coli. This study is a laboratory experimental research with a Post-Test Only Control Group Design design consisting of five treatment groups, namely negative control, positive control, and three treatment groups with a dose of kepok banana peel extract of 300 mg, 600 mg, and 900 mg. Each group consisted of five male white rats. Data on the number of leukocytes was obtained from the results of blood tests after treatment, then analyzed using the one-way ANOVA test and followed by the Post Hoc Tukey test. The results showed that the administration of kepok banana peel extract had a significant effect on reducing the number of leukocytes (p < 0.05), with a dose of 600 mg providing the most optimal effect. The conclusion of this study is that kepok banana peel extract is effective in normalizing the number of Escherichia coli-induced white mouse leukocytes.